ANALISIS KESALAHAN SISWA PADA MATERI KUBUS & BALOK - Rokan, Najwah; Putri, Jihan Hidayah (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2023)
Researchers conducted research that aims to find out the problems faced by students when learning mathematics, which are the factors that cause errors in solving math problems. This error factor must be known so that it is easier to get solutions and parts that need to be emphasized during learning. This research is a qualitative descriptive study to analyze and describe the types of mistakes students make when working on cube and block math questions. The subjects of this study were 30 students of SMP Al Washliyah 8 Medan in class VIII-A. The written test is a data collection technique. The results of the student error analysis obtained: 1) 66.67% conceptual errors with a